A global genomic perspective on the multidrug-resistant Streptococcus pneumoniae 15A-CC63 sub-lineage following pneumococcal conjugate vaccine introduction. Issue 4 (21st April 2023) - Hawkins, Paulina A.; Chochua, Sopio; Lo, Stephanie W.; Belman, Sophie; Antonio, Martin; Kwambana-Adams, Brenda; von Gottberg, Anne; du Plessis, Mignon; Cornick, Jen; Beall, Bernard; Breiman, Robert F.; Bentley, Stephen D.; et al.
Abstract : The introduction of pneumococcal conjugate vaccines (PCV7, PCV10, PCV13) around the world has proved successful in preventing invasive pneumococcal disease. However, immunization against Streptococcus pneumoniae has led to serotype replacement by non-vaccine serotypes, including serotype 15A. Clonal complex 63 (CC63) is associated with many serotypes and has been reported in association with 15A after introduction of PCVs. A total of 865 CC63 isolates were included in this study, from the USA ( n =391) and a global collection ( n =474) from 1998–2019 and 1995–2018, respectively. We analysed the genomic sequences to identify serotypes and penicillin-binding protein (PBP) genes 1A, 2B and 2X, and other resistance determinants, to predict minimum inhibitory concentrations (MICs) against penicillin, erythromycin, clindamycin, co-trimoxazole and tetracycline. We conducted phylogenetic and spatiotemporal analyses to understand the evolutionary history of the 15A-CC63 sub-lineage. Overall, most (89.5 %, n =247) pre-PCV isolates in the CC63 cluster belonged to serotype 14, with 15A representing 6.5 % of isolates. Conversely, serotype 14 isolates represented 28.2 % of post-PCV CC63 isolates ( n =618), whilst serotype 15A isolates represented 65.4 %. Dating of the CC63 lineage determined the most recent common ancestor emerged in the 1980s, suggesting the 15A-CC63 sub-lineage emerged from its closest serotype 14 ancestor prior to the development of pneumococcal vaccines. This sub-lineage was predominant in the USA, Israel and China. Multidrug resistance (to three or more drug classes) was widespread among isolates in this sub-lineage. We show that the CC63 lineage is globally distributed and most of the isolates are penicillin non-susceptible, and thus should be monitored.